2008
DOI: 10.4103/0973-1229.36504
|View full text |Cite
|
Sign up to set email alerts
|

Positive Emotions, Spirituality and the Practice of Psychiatry

Abstract: This paper proposes that eight positive emotions: awe, love (attachment), trust (faith), compassion, gratitude, forgiveness, joy and hope constitute what we mean by spirituality. These emotions have been grossly ignored by psychiatry. The two sciences that I shall employ to demonstrate this definition of spirituality will be ethology and neuroscience. They are both very new. I will argue that spirituality is not about ideas, sacred texts and theology; rather, spirituality is all about emotion and social connec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
4

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 20 publications
(22 reference statements)
1
24
0
4
Order By: Relevance
“…29, 31 Vaillant used arguments pertaining to genetic evolution and language development, to propose the maturation of human spirituality as the "third" human evolutionary process. [97][98] He suggested that three evolutions could be identified, the genetic (Darwinian) evolution, a cultural evolution (mediated by the development of language) and then the maturation of human spirituality. Anandarajah described two multidimensional models for spirituality applicable across culture and belief systems that could be used for patient care, education and research.…”
Section: Reality Of Spirituality and Religion For Practitioners And Umentioning
confidence: 99%
“…29, 31 Vaillant used arguments pertaining to genetic evolution and language development, to propose the maturation of human spirituality as the "third" human evolutionary process. [97][98] He suggested that three evolutions could be identified, the genetic (Darwinian) evolution, a cultural evolution (mediated by the development of language) and then the maturation of human spirituality. Anandarajah described two multidimensional models for spirituality applicable across culture and belief systems that could be used for patient care, education and research.…”
Section: Reality Of Spirituality and Religion For Practitioners And Umentioning
confidence: 99%
“…Dr. Vaillant urges everyone to "[w]orry less about cholesterol and more about gratitude and forgiveness." 39 Dr. Vaillant equates the innate positive emotions of awe, love (attachment), trust (faith), compassion, gratitude, forgiveness, joy, and hope with spirituality 40. …”
mentioning
confidence: 99%
“…Humanistic psychology (Maslow, 1954(Maslow, , 1976Rogers, 1964) acknowledges that spirituality is woven into the very fabric of human existence; however, this article furthers the position that the human striving for love and connection is the very definition of human spirituality (Vaillant, 2008a(Vaillant, , 2008b; see also, Saroglou, Buxant, & Tilquin, 2008). By suggesting that the original human intention to connect re-emerges in each subsequent developmental stage, merely reconfiguring to fit the requirements of current developmental tasks, it argues that the early family is an important arbiter of human spirituality across the lifespan.…”
Section: Introductionmentioning
confidence: 90%
“…Love is expansive The Family Sanctum 245 and makes us flexible, creative, and more integrated (Isen, Rosenzweig, & Young, 1991;Panksepp, 1998;Lyubomirsky & King, 2005), whereas negative emotions such as fear and anxiety narrow our attention to the self (Fredrickson, 2004) and are about individual survival in the present moment. Vaillant (2008a) argues through a review of neuroscience that our brains are hardwired to generate positive emotions; we need only to recognize them as relevant for our spirituality and continued evolution. He writes that human spirituality is our "evolutionary press towards connection and communitybuilding .…”
Section: The Extension Of Love As An End In Itself Across the Lifespanmentioning
confidence: 99%